IYRP Global Alliance: Roadmap for IYRP 2026 - Samuels, I. (Agricultural Research Council, South Africa, 2025)
A presentation made by the Chair of the International Year of Rangelands and Pastoralists 2026 Global Alliance introducing the year, the Global Alliance and the Roadmap to and through 2026. The presentation was made at a webinar organised by the CGIAR Science Program on Multifunctional Landscapes to raise awareness about the year amongst the CGIAR.